A combined physiological and biophysical approach to understand the ligand‐dependent efficiency of 3‐hydroxy‐4‐pyridinone Fe‐chelates. (16th August 2020) - Santos, Carla S.; Leite, Andreia; Vinhas, Sílvia; Ferreira, Sofia; Moniz, Tânia; Vasconcelos, Marta W.; Rangel, Maria
Abstract: Ligands of the 3‐hydroxy‐4‐pyridinone (3, 4‐HPO) class were considered eligible to formulate new Fe fertilizers for Iron Deficiency Chlorosis (IDC). Soybean ( Glycine max L.) plants grown in hydroponic conditions and supplemented with Fe‐chelate [Fe(mpp)3 ] were significantly greener, had increased biomass, and were able to translocate more iron from the roots to the shoots than those supplemented with an equal amount of the commercially available chelate [FeEDDHA]. To understand the influence of the structure of 3, 4‐HPO ligand on the role of the Fe‐chelate to improve Fe‐uptake, we investigated and report here the effect of Fe‐chelates ([Fe(mpp)3 ], [Fe(dmpp)3 ], and [Fe(etpp)3 ]) in addressing IDC. Chlorosis development was assessed by measurement of morphological parameters, quantification of chlorophyll and Fe, and other micronutrient contents, as well as measurement of enzymatic activity (FCR) and gene expression (FRO2, IRT1, and Ferritin). All [Fe(3, 4‐HPO)3 ] chelates were able to provide Fe to plants and prevent IDC but with a different efficiency depending on the ligand. We hypothesize that this may be related with the distinct physicochemical characteristics of ligands and complexes, namely, the diverse hydrophilic–lipophilic balance of the three chelates. To test the hypothesis, we performed an EPR biophysical study using liposomes prepared from a soybean ( Glycine3 max L.) lipid extract and spin probes. The results showed that the most effective chelate [Fe(mpp)3 ] shows a preferential location close to the surface while the others prefer the hydrophobic region inside the bilayer. Significance statement: The 3‐hydroxy‐4‐pyridinone Fe‐chelates, [Fe(mpp)3 ], [Fe(dmpp)3 ], and [Fe(etpp)3 ], were all able to provide Fe to plants and prevent IDC. Efficacy is dependent on the structure of the ligand. From an EPR biophysical study using spin probes and liposomes, prepared from a soybean lipid extract, we hypothesize that this may be related with the distinct preferential location close to the surface or on the hydrophobic region of the lipid bilayer. [Fe(mpp)3 ] provide higher amounts of Fe in the leaves. Abstract :